CONTENTS OF EXCHANGEABLE CATIONS OF SOILS FORMED UPON LIMESTONES AND DOLOMITES - M. MARKOSKI , G. BAROVIC , T. MITKOVA , V. TANASKOVIC , V. SPALEVIC (Journal of Environmental Protection and Ecology 19, No 1, 127–138 (2018), 2018)
Contents of exchangeable cations of the soils formed upon limestones and dolomites were examined at 52 sites on the slopes of the Mount Massive of Galicica (40°56′29.7″N 20°48′22.5″E), Jablanica (41°12′17.4″N 20°34′19.8″E), Suva Gora (41°49′06.4″N 21°05′27.5″E), Ilinska Planina (41°18’04.7″N 20°58’08.5″E) and in the region of Doiran Lake (41°11′21.3″N 22°43′14.4″E). The research results show that 34 profiles are with Rendzic Leptosols, 13 with Chromic Leptic Luvisol on hard limestones and 5 profiles of Rhodic Leptic Luvisol on hard limestones. The exchangeable basic cations are determined by the method of Hendershot and Duquette (1986) and exchangeable acid cations by the Melich method (1948). The research show that these soils have high cation ex change capacities (CEC), which vary in wide ranges, from 24.69 to 99.39 cmol (+) kg–1. The high values of the CEC are the result of the high content of clay and organic matter. The values of total exchangeable bases (S) and degree of base saturation (V) indicated that the CEC is highly saturated with basic cations. The exchangeable Ca2+ is dominant in the adsorptive complex (average 59%) and further follow H+ + Al3+ (average 27%), Mg2+ with 13% and K+ and Na+ with less than 1% of CEC
Keywords: Rendzic Leptosols, Chromic Leptic Luvisol and Rhodic Leptic Luvisol on hard limestones, exchangeable cations: Ca2+, Mg2+, K+, Na+, H+ + Al3+